Renal Involvement in Hospitalized COVID-19 Patients without Pre-existing Kidney Disease (Bangladesh Renal Journal, 2026)
Introduction: COVID 19, caused by the highly contagious SARS CoV 2 virus, has resulted in over 6 million deaths worldwide since December 2019. While primarily affecting the pulmonary system, the infection also impacts kidneys. Increasing evidence shows increasing renal impairment among hospitalized COVID-19 patients, highlighting the importance of monitoring renal functions and its association with COVID-19 disease severity.Materials & Methods: This prospective observational study was conducted at Bangladesh Medical University (BMU), from September 2020 to August 2021, involving 231 adult COVID-19 patients with normal baseline serum creatinine. Patients with pre-existing conditions or unwilling to consent were excluded. Relevant data were collected and statistical analysis was conducted.Results: The study population had a mean age of 53.5 ± 14.5 years, with 48.1% participants aged 51–70 years; males comprised 57.1%, and mean BMI was 23.3 kg/m². Fever was the predominant symptom (93.9%), followed by cough (68.8%), loss of smell (50.2%), shortness of breath (45%), diarrhea (37.7%), and body ache (22.5%). Mean SpO‚ was 93.17 ± 4.21%. Hypertension (29.9%) and diabetes (22.1%) were the most common comorbidities. HRCT revealed 26–50% lung involvement in 44.5% and 51–75% in 35.5% of patients. Average time from symptom onset to admission was 5.9 ± 2.3 days, with hospital stay averaging 13.1 ± 5.3 days. COVID-19 disease severity was moderate in 66.2%, severe in 16.9%, and critical in 5.2%. Renal complications were frequent: AKI occurred in 11.7%, proteinuria and hematuria each in 25.1%, and overall renal involvement in 55.8%. Critical cases showed the highest renal involvement (77.8%), followed by severe (76.9%) and moderate (51%).Conclusion: There is significant impact of COVID-19 on renal function and monitoring renal involvement in hospitalized COVID-19 patients is vital for good prognosis.Bang. Renal J. 2026; 8(1): 3-9